Strain-Induced Tailoring of Oxygen-Ion Transport in Highly Doped CeO2 Electrolyte: Effects of Biaxial Extrinsic and Local Lattice Strain - Ahn, Junsung; Choi, Sungjun; Yoon, Kyung Joong; Son, Ji-Won; Kim, Byung-Kook; Lee, Jong-Ho; Jang, Ho Won; Kim, Hyoungchul (American Chemical Society, 2017)
We explored oxygen-ion transport in highly doped CeO2 through density-functional theory calculations. By applying biaxial strain to 18.75 mol % Ceo(2):Gd, we predicted the average migration-barrier energy with six different pathways, with results in good agreement with those of experiments. Additionally, we found that the migration-barrier energy could be lowered by increasing the tetrahedron volume,, including the space occupied by the oxygen vacancy. Our results indicate that the tetrahedron volume can be expanded by larger codoliants, as well as biaxial tensile strain: Thus, the combination of thin-film structure and codoping could offer a new approach to accelerate oxygen-ion transport.
Keywords: THIN-FILM; ELECTRICAL-PROPERTIES; ENERGY-CONVERSION; CERIA SYSTEM; CONDUCTIVITY; DEPOSITION; MEMBRANES; SAMARIUM; OXIDES; ND3+